Ir-O-Mn embedded in porous nanosheets enhances charge transfer in low-iridium PEM electrolyzers - Dawei Wang; Fangxu Lin; Heng Luo; Jinhui Zhou; Wenshu Zhang; Lu Li; Yi Wei; Qinghua Zhang; Lin Gu; Yanfei Wang; Mingchuan Luo; Fan Lv; et al. (Nature Communications)
Abstract Using metal oxides to disperse iridium (Ir) in the anode layer proves effective for lowering Ir loading in proton exchange membrane water electrolyzers (PEMWE). However, the reported low-Ir-based catalysts still suffer from unsatisfying electrolytic efficiency and durability under practical industrial working conditions, mainly due to insufficient catalytic activity and mass transport in the catalyst layer. Herein we report a class of porous heterogeneous nanosheet catalyst with abundant Ir-O-Mn bonds, achieving a notable mass activity of 4 A mgIr −1 for oxygen evolution reaction at an overpotential of 300 mV, which is 150.6 times higher than that of commercial IrO2. Ir-O-Mn bonds are unraveled to serve as efficient charge-transfer channels between in-situ electrochemically-formed IrOx clusters and MnOx matrix, fostering the generation and stabilization of highly active Ir3+ species. Notably, Ir/MnOx-based PEMWE demonstrates comparable performance under 10-fold lower Ir loading (0.2 mgIr cm−2), taking a low cell voltage of 1.63 V to deliver 1 A cm−2 for over 300 h, which positions it among the elite of low Ir-based PEMWEs.